Effectiveness of the pH Master Application on Acid-Base Concepts as a Digital Alternative to Conventional Laboratory Practices for Enhancing Student Learning Outcomes" - Agnys Dewi Kusumawati; Sri Retno Dwi Ariani; Nurma Yunita Indriyanti (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2024)
Traditional Chemistry Laboratories, such as acid-base reactions, are hard to demonstrate for present-day students in their lab classes when they need to have the knowledge exchange we had, graduating (and teaching) with mortar boards lined up and ready for weddings. The Evaluation Of The Digital Platform “pH Master” For Enhancing Chemistry Student Performance Through A Virtual Imitation of Traditional Lab Practices The study used Akker's research and development model, including initial studies, product design, testing products, and trials. Validation was done using the Aiken formula by two expert validators and three practitioners for all items with a V value greater than 0.87. Surveys for needs analysis involved 45 students, and the learning effects were assessed with 90 students across three schools. Results Students responded favourably to the pH Master app and perceived ineffable pedagogical value. Most students agreed on the necessity of doing practical activities about what was being learned, and almost all also had trouble understanding study materials specifically related to acids and bases. The results showed a statistically higher mean n-gain value in the experimental group than in control one (0.6622 versus 0.5691) by independent t-test across three schools at p < 0,001 significance level between the two groups. This then confirms that the media created did support student learning. This study highlights the potential of the pH Master app to enhance student learning experience and active involvement in chemical education, which suggests a promising approach towards digitalising conventional practical work.